2011
DOI: 10.1089/scd.2010.0205
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Impairs Skeletogenesis from Embryonic Stem Cells by Affecting Osteoblast and Osteoclast Differentiation

Abstract: High maternal blood glucose levels caused by diabetes mellitus can irreversibly lead to maldevelopment of the growing fetus with specific effects on the skeleton. To date, it remains controversial at which stage embryonic development is affected. Specifically during embryonic bone development, it is unclear whether diminished bone mineral density is caused by reduced osteoblast or rather enhanced osteoclast function. Therefore, the aim of this study was to characterize the growth as well as the skeletal differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 45 publications
4
46
1
3
Order By: Relevance
“…We did not observe altered osteoclast functions ex vivo, in contrast to other reports, which suggested that a diabetic microenvironment tends to inhibit osteoclast differentiation and function (30,16,29,4,12). However, none of these studies used an in vivo model of rats with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not observe altered osteoclast functions ex vivo, in contrast to other reports, which suggested that a diabetic microenvironment tends to inhibit osteoclast differentiation and function (30,16,29,4,12). However, none of these studies used an in vivo model of rats with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
“…In vivo, Kawashima et al (17) found evidence supporting increased osteoclastogenesis in the diabetic bone microenvironment (17). In vitro, Huang et al (18) reported that an elevated insulin environment negatively regulated osteoclast differentiation and the expression of RANK and c-fos (18), and these results were corroborated by a study by Dienelt and zur Nieden (19). The data from the present study suggest that bone resorption was impaired in the T2DM model due to impaired osteoclast function.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the malformation rate is clearly correlated with increased glucose concentrations (Jawerbaum and White 2010). Experimental results support the notion of hyperglycemia as a teratogen, since high glucose levels (Dienelt and Zur Nieden 2011) or maternal diabetes in vivo as well as exposure to high glucose concentration cause embryonic maldevelopment. Several studies have shown that fetuses from mild diabetic rats have a compromised intrauterine development (Saito et al 2010;Iessi et al 2010) and elevated oxidative stress, contributing to an increased incidence of skeletal and visceral malformations at birth .…”
Section: Discussionsupporting
confidence: 64%